Building a flagellum in biological outer space - Lewis D. B. Evans; Colin Hughe; Gillian M. Fraser (Microbial Cell)
Flagella, the rotary propellers on the surface of bacteria, present a paradigm for how cells build and operate complex molecular ‘nanomachines’. Flagella grow at a constant rate to extend several times the length of the cell, and this is achieved by thousands of secreted structural subunits transiting through a central channel in the lengthening flagellum to incorporate into the nascent structure at the distant extending tip. A great mystery has been how flagella can assemble far outside the cell where there is no conventional energy supply to fuel their growth. Recent work published by Evans et al.[Nature (2013) 504: 287-290], has gone some way towards solving this puzzle, presenting a simple and elegant transit mechanism in which growth is powered by the subunits themselves as they link head-to-tail in a chain that is pulled through the length of the growing structure to the tip. This new mechanism answers an old question and may have resonance in other assembly processes.